Perlindungan Hukum Konsumen Terhadap Kandungan Bahan Makanan Dan Minuman Berbahaya Ditinjau Dari Peraturan Bpom Dan Undang-Undang Perlindungan Konsumen - Subiyakto*, Aries; Markoni, Markoni; Widarto, Joko; Nardiman, Nardiman (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The background of this research is because of the BPOM findings which reveal that syrup drugs circulating in the market contain the dangerous substances ethylene glycol (EG) and diethylene glycol (DEG). Law Number 8 of 1999 which is one of the bases in efforts to realize consumer legal protection of their rights, clear and correct information is needed regarding the safety and security of consumers in consuming drugs and the responsibility of manufacturers or distributors regarding defective products or dangerous. The emergence of this issue raises concerns among the public and causes losses for pharmacies or drugstores that sell syrup drugs. This research is a quantitative research using a normative approach. The research was carried out by studying laws and regulations, books, and journals (library research) related to BPOM's supervision of the distribution of drugs containing dangerous substances. The results of the study show that BPOM's supervision of the spread of drugs with dangerous ingredients is by carrying out field inspections and actions, product withdrawals and destruction, carrying out legal proceedings, revising regulations, educating the public. BPOM provides legal protection to the public only when consuming food that has a distribution permit, if the food does not have a distribution permit Loka BPOM only protects morally by educating the public.